2007
DOI: 10.1037/0090-5550.52.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Family caregivers of persons with spinal cord injury: Predicting caregivers at risk for probable depression.

Abstract: Objective-To determine the percentage of family caregivers of persons with spinal cord injury (SCI) with probable depression and to test the hypothesis that dysfunctional problem-solving abilities would be significantly predictive of risk status after taking into account important demographic characteristics and caregiver health.Design-Correlational and logistic regression analyses of data collected in a cross-sectional design.Participants-Eighteen men and 103 women caregivers (mean age of caregivers = 45.66 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 49 publications
5
68
1
1
Order By: Relevance
“…2,21 This study did not find any significant relationship between the level of injury and the caregiver burden, and is similar to the findings reported in other nonWestern countries. 7,22 This could be because of the fact that the majority of the paraplegic persons, who were expected to be independent in self-care and mobility, suffered from moderate-to-severe disability requiring assistance in many ADL.…”
Section: Discussionsupporting
confidence: 89%
“…2,21 This study did not find any significant relationship between the level of injury and the caregiver burden, and is similar to the findings reported in other nonWestern countries. 7,22 This could be because of the fact that the majority of the paraplegic persons, who were expected to be independent in self-care and mobility, suffered from moderate-to-severe disability requiring assistance in many ADL.…”
Section: Discussionsupporting
confidence: 89%
“…However, family caregivers of individuals with orthopedic disability also undergo various dif ficulties themselves; they experience financial strain (Sav et al, 2013), health problems resulting from caregiving such as pain and disruptions in the func tioning of the cardiovascular and immune systems (Donelan et al, 2002;Vitaliano, Zhang, & Scanlan, 2003), elevated levels of distress (Chan, Lee, & Lieh Mak, 2000), anxiety, and a lower quality of life (Elliott & Berry, 2009). Family caregivers who report a great er caregiving burden have a greater tendency to feel decreased life satisfaction and high levels of depres sion (Dreer, Elliott, Shewchuk, Berry, & Rivera, 2007;Unalan et al, 2001). They are also more likely to have negative attitudes towards their family member with disability (Elliott & Pezent, 2008), which disrupts the positive family environment.…”
Section: Familial Factors Associated With Depressive Feelings In Peopmentioning
confidence: 99%
“…Therefore, there is usually a family caregiver who lives with people with orthopedic disabilities and interacts with them on a daily basis (Dreer, Elliott, Shewchuk, Berry, & Rivera, 2007). Due to such a living arrangement that requires continual interaction between the indi vidual with disability and his/her relative, the char acteristics and functioning of the caregiving family member might be among the factors affecting the emotional wellbeing of individuals with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Armstrong goes on to state that the spouse's mourning, difficulty of assuming a providing role, as well as possible changes in sexual relationships are often not acknowledged by the caregiver or patient. Dreer et al (2007) reported that depression was higher in caregivers of patients with SCI than in a non-SCI population. They suggest that role overload, lack of information, financial strain, impaired quality of life, change in health status, and emotional problems all contribute to the caregiver's increased vulnerability to depression.…”
Section: Models Of Social Supportmentioning
confidence: 99%
“…Depression is examined in relation to adult attachment anxiety and avoidance, perceived social support, and proposed as a measurement of the absence of resilience. Specifically, the acquisition of a disability can negatively impact social support, increase the likelihood of experiencing depression, and activate the attachment system (Armstrong, 1991;Dreer, Elliott, Shewchuk, & Berry, 2007;Gan & Schuller, 2002). The possible relationships between sustaining a disability and attachment strategies, social support, resilience, and depression are integrated throughout the chapter.…”
Section: Dodd Zane Effects Of Adult Romantic Attachment and Social mentioning
confidence: 99%